How Secondary Students Develop Grammar Skills through Integrated- Skill Activities - Hnin Ze Khine; Hnin Ze Hlaing (Winaya Inspirasi Nusantara Foundation, 2026)
Traditional English language pedagogy often treats grammar as isolated units of declarative knowledge, failing to foster real-time communicative proficiency during authentic production. To address this issue, this study investigated the effectiveness of an integrated-skill approach in teaching eight specific grammar patterns and explored student attitudes toward this framework. A quantitative quasi-experimental research design was implemented with twenty Secondary I English as a Foreign Language (EFL) learners at a private language center in Myanmar over a three-month instructional intervention. Data were collected using diagnostic pre-tests, identical parallel post-tests, and two multi-item closed-ended questionnaires, and analyzed using descriptive and inferential statistics. The empirical findings from a paired-samples t-test demonstrated a statistically significant improvement in overall morphosyntactic competence from the pre-test (M = 15.05) to the post-test (M = 32.55; p < .001). However, granular structural analysis revealed that development was not uniform. Rule-governed structures like the present simple passive and exclamations showed substantial accuracy gains, whereas lexically complex items like past participles experienced a clear performance plateau. Perceptually, the multi-skill task framework generated highly positive attitudes by increasing classroom interaction, though a notable paradox emerged as learners frequently experienced cognitive processing strains during dense receptive input activities. These outcomes imply that the conversion of declarative knowledge into automatic performance depends heavily on structural complexity. Curriculum designers and educators must systematically combine communicative fluency with guided, explicit focus-on-form interventions to ensure that young learners actively notice and process difficult syntactic patterns during multi-skill tasks.